HUBUNGAN TERPAAN IKLAN OPPO SMARTPHONE DAN INTENSITAS WORD OF MOUTH DENGAN MINAT BELI PRODUK OPPO - Muhammad Sahil; Djoko Setyabudi (Interaksi Online, 2019)
Active smartphone users in Indonesia from year to year have always experienced a significant increase. Oppo costs an advertisement of 461 billion rupiah for ad spending. But according to data from IDC in terms of Oppo sales only able to rank third. Besides advertising, word of mouth communication also has a role in a decision that will be taken by consumers. Because if information about the product is discussed continuously from consumers with one another, it can cause a feeling of attitude towards a product. This study aims to determine the relationship between Oppo smartphone advertising and the intensity of word of mouth with interest in buying Oppo products, using non-probability sampling technique with a total sample of 50 respondents from the city of Semarang with the age requirement of respondents, 18-25 years old, knowing Oppo ads smartphone and Oppo product information. The results of this study there is a relationship between exposure to advertising and buying interest, using the advertising exposure theory as evidenced by the analysis of Kendall’s Tau-b produces a significance number of 0,000 or stated to be very significant and a correlation value of 0.526. This study also found that there was a correlation between the intensity of word of mouth and the interest in buying products. The relationship of these two variables uses the theory of the buyer information environment, namely by analyzing the Kendall’s Tau-b correlation to produce a significance value of 0,000 or significant and the correlation coefficient of 0,499, which means there is a relationship between these variables.